Board of Commissioners and Corporate Social Responsibility Disclosure: The Role of Corporate Performance As Moderation - Putra, Defriko Gusma; Saputra, Syailendra Eka; Setiawan, Puguh; Susanti, Nora; Syamra, Yesmira (Universitas Muhammadiyah Semarang, 2023)
This research has the desire to prove the role of financial performance in strengthening the relationship between the role of the board of commissioners of liquidity and CSR. Research was conducted on consumer sector companies in the Indonesian capital market. The research was carried out from 2017 – 2021. The data analysis method used is Moderating Regression Analysis (MRA). The process of statistical testing is done with the help of STATA. The result of founding independent commissioners' roles and liquidity has a positive effect on CSR disclosure, besides that company performance which functions as a moderating variable also has a positive effect on company performance. In testing the moderating effect it was found that the company's performance weakened the relationship between liquidity and CSR, while the second test found that the company's performance strengthened the board of commissioners' relationship with CSR disclosure in consumers of good companies in the Indonesian Stock Market, Theoretically, our research will contribute to the development of the concept of green accounting and governance, which of course will encourage increased corporate reputation, besides that practically our research results can be used as a policy reference for public companies in Indonesia in increasing the implementation of environmental, social and environmental responsibility values governance.